Heavily Indebted Poor Countries Initiative : Statistical Update. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
This document updates the information provided in the September 2005 Heavily Indebted Poor Countries (HIPC) Initiative - Status of Implementation report. It deals exclusively with the enhanced HIPC Initiative, and does not consider the implications of the Multilateral Debt Relief Initiative (MDRI).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet